PEMBERIAN PUPUK NPKMg (15-15-6-4) DAN INTERVAL WAKTU PEMBERIAN PUPUK PELENGKAP CAIR TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Untung, Rahmat; ', Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to determine the best combination of NPKMg  fertilizer and this application interval of supplementary liquid fertilizer on the growth of palm oil seedling in the main nursery. The study was conducted in factorial experiment in the form of 4 × 4 by using a complete randomized design (CRD), which consists of two factors. The first factor is the application of fertilizer NPKMg  with 4 levels, namely: M0: Without Fertilizer NPKMg, M1: Fertilizer NPKMg 4 g/polybag/week, M2: Fertilizer NPKMg             5 g/polybag/weeks, M3: Fertilizer NPKMg 6 g/polybag/week. The second factor is the interval application of Complementary Liquid Fertilizer with 4 levels, namely: F0: Without Complementary Liquid Fertilizer, F1: 10 days, F2: 20 days, F3: 30 days. Such experiments are 16 treatment and each treatment was repeated 3 times so that there are 48 units experiment. Each experimental unit consisted of two plants so wholly obtained 96 plants. Parameters measured were the increase of seedling height, the number of leaves, the increase in diameter stump, the ratio of crown roots and dry weight. The results showed that the combination of NPKMg fertilizer application 4 g/polybag/week and the time interval of 10 days each application complementary liquid fertilizer is the best treatment.   Keywords: Palm Oil, NPKMg Fertilizer, Complement Liquid Fertilizer